The current state of the saiga (Saiga tatarica L.) population in Betpak-Dala (Kazakhstan) - Myrzabayev, Amanay; Ibraibekov, Zhanbolat; Bodeev, Marat; Britko, Valery; Yelshina, Kymbat; Tilla, Zhansaya; Gongalsky, Konstantin (Acta Scientiarum. Animal Sciences, 2024)
The objective of this research is to address saiga conservation challenges amid significant anthropogenic pressures through a population model-based approach. The study involved an analysis of herd composition in terms of sex, age, and size over the years 2019-2022, with a focus on lamb weight measurements in 2022. Notably, 2021 witnessed a substantial decline in offspring numbers, with lambs being three times scarcer compared to 2020 and 5.2 times fewer than in 2022 (p ≤ 0.05). Male saigas exhibited a 3.1-fold reduction in birth rates in 2021 relative to 2020 and a 5.6-fold decrease compared to 2022 (p < 0.05). The fluctuations in the number of females and males across the three years were found to be statistically comparable (p ≥ 0.05). Since 2022, there has been a notable increase in the size of saiga herds, with counts reaching 450-500 animals compared to 2019-2020 (p ≤ 0.05). The observation identified a total of 93 saiga herds, with six of them consisting of more than 1,000 antelopes. The augmentation of male presence within herds is anticipated to contribute to sustaining saiga population growth. Achieving this outcome may necessitate the implementation of captive breeding initiatives or an integrated approach.